NTRK-rearranged Cervical Sarcoma: Expanding the Clinicopathologic Spectrum. (January 2021) - Hodgson, Anjelica; Pun, Cherry; Djordjevic, Bojana; Turashvili, Gulisa
Abstract : The NTRK genes ( NTRK1, NTRK2, and NTRK3 ) encode for TrkA, TrkB, and TrkC, neurotrophic tyrosine receptor kinases which serve a variety of functions including in the regulation of pathways involved in carcinogenesis. A number of reports have described NTRK gene fusions in a variety of adult and pediatric tumor types from various organ systems including the central nervous system, thyroid gland, breast, and soft tissue. NTRK -rearranged uterine sarcomas are a recently described group of tumors which occur in both the uterine corpus and cervix, tend to morphologically resemble fibrosarcoma, and may behave aggressively, although data is limited given the newly recognized nature and thus relative rarity of these tumors. Herein, we present the case of a cervical sarcoma with SPECC1L-NTRK3 fusion (detected with Illumina RNA Fusion Panel), prospectively diagnosed at the time of cervical biopsy and subsequently treated with hysterectomy. The clinical presentation, radiologic findings, morphologic features, and immunohistochemical profile of this case will be reviewed and compared with the body of existing literature to date. Identification of NTRK -rearranged neoplasms is important as targeted therapy in the form of NTRK inhibitors has recently become widely available.